A freeze-fracture study on the developing satellite cells of spinal ganglia in the chick embryo - Claudio A. Ferraz de Carvalho; Ciro F. da Silva (Arquivos de Neuro-Psiquiatria, 1988)
A freeze-fracture analysis of the satellite cells of spinal ganglia of the chick embryo was performed in 8 successive stages of development, from the 5th incubation day to hatching. The characteristic laminar disposition of the cells were first observed on the 7th day. Tight junctions were found at the 20th incubation day. Small groups or irregular aggregates of particles, but not gap junctions, were described on the 7th and 8th days. Pinocytotic vesicles were pointed out in the different stages considered.